Genetic Evaluation of the Patients with Clinically Diagnosed Inborn Errors of Immunity by Whole Exome Sequencing: Results from a Specialized Research Center for Immunodeficiency in Türkiye (vol 44, 157, 2024) - Erman, Baran; Aba, Umran; Ipsir, Canberk; Pehlivan, Damla; Aytekin, Caner; Cildir, Gokhan; Tezcan, Ilhan (Springer/Plenum Publishers, 2024)
[Abstract Not Available]